Growth and oxidation of graphene on Rh(111) - Gotterbarm, Karin; Zhao, Wei; Höfert, Oliver; Gleichweit, Christoph; Papp, Christian; Steinrück, Hans-Peter (Physical Chemistry Chemical Physics, 2013)
The growth and oxidation of graphene supported on Rh(111) was studied in situ by high-resolution X-ray photoelectron spectroscopy. By variation of propene pressure and surface temperature the optimum growth conditions were identified, yielding graphene with low defect density. Oxidation of graphene was studied at temperatures between 600 and 1000 K, at an oxygen pressure of ∼2 × 10 mbar. The oxidation follows sigmoidal reaction kinetics. In the beginning, the reaction rate is limited by the number of defects, which represent the active sites for oxygen dissociation. After an induction period, the reaction rate increases and graphene is rapidly removed from the surface by oxidation. For graphene with a high defect density we found that the oxidation is faster. In general, a reduction of the induction period and a faster oxidation occur at higher temperatures. © 2013 The Owner Societies.